Overcoming Constipation in Stroke Patients Using the I Love You and Swedish Massage Techniques - Suantika, Putu Inge (STIKep PPNI Jawa Barat, 2025)
Aims: This study aims to determine the effectiveness of a combination of the I LOVE YOU and Swedish techniques in relieving constipation in stroke patients. Methods: This study employed a quasi-experimental design with a pre-post test in a single-group setting, involving 30 stroke patients. The intervention consisted of abdominal massage therapy using a combination of the I LOVE YOU and Swedish techniques, applied twice daily for 30 minutes over three consecutive days. The Bristol Stool Scale and a 5-point Likert scale for patient constipation assessment were used to measure outcomes. Descriptive statistics and the Wilcoxon test were applied to analyze the data. Results: The findings indicated that the combination of the I LOVE YOU and Swedish techniques significantly improved bowel movements and reduced constipation in stroke patients, as evidenced by the Wilcoxon test results. Conclusion: This study demonstrates that non-pharmacological abdominal massage techniques using the I LOVE YOU and Swedish methods can serve as effective alternatives for managing constipation in stroke patients.